Integrated high-throughput analysis identifies super enhancers in metastatic castration-resistant prostate cancer - Zeng, Jie; Chen, Jiahong; Li, Maozhang; Zhong, Chuanfan; Liu, Zezhen; Wang, Yan; Li, Yuejiao; Jiang, Funeng; Fang, Shumin; Zhong, Weide (Frontiers in Pharmacology, 2023)
Background: Metastatic castration-resistant prostate cancer (mCRPC) is a more aggressive stage of prostate cancer, and a powerful prediction model is lacking. Epigenetic programming is a mechanism of mCRPC development. Super enhancers (SEs), epigenetic elements, are involved in multiple tumor-promoting signaling pathways. However, the SE-mediated mechanism in mCRPC remains unclear. Methods: SE-associated genes and TFs were identified from a cell line (C4-2B cells) of mCRPC by the CUT&Tag assay. Differentially expressed genes (DEGs) between mCRPC and primary prostate cancer (PCa) samples in the GSE35988 dataset were identified. A biochemical recurrence (BCR) risk prediction model was constructed based on the overlapping genes (termed SE-associated DEGs). To confirm the key SE-associated DEGs, BET inhibitor JQ1 was applied to cells to block SE-mediated transcription. Finally, single-cell analysis was performed to visualize cell subpopulations expressing the key SE-associated DEGs. Results: Nine human TFs, 867 SE-associated genes and 5417 DEGs were identified. The prediction model based on the 142 overlapping SE-associated DEGs showed excellent performance. Time-dependent receiver operating characteristic (ROC) curve analysis showed strong predictive power at 1 year (0.80), 3 years (0.85), and 5 years (0.88). The high-risk group in the Taylor cohort showed a significantly worse outcome. The TF regulatory network showed that the AR/FKBP5 axis could be promoted by SEs. In addition, FKBP5 activity was significantly inhibited by JQ1. Single-cell analysis revealed that FKBP5 was mainly expressed in PCa cells. Conclusions: We screened out SEs involved with mCRPC cell and provided potential clinical translation of SEs.